2012
DOI: 10.1590/s0102-36162012000600010
|View full text |Cite
|
Sign up to set email alerts
|

Associação clínico-radiográfica do índice acromial e do ângulo de inclinação lateral do acrômio

Abstract: Objective: To evaluate the clinical-radiographic subacromial disease symptoms correlated with adaptation of the measure of lateral acromion angle and its respective measuring radiographic acromial index. Methods: In the period between october 2010 and february 2011 were evaluated 55 painful shoulders with Neer test and true anteroposterior radiography. Patients were divided into two groups, with Neer test positive and negative. The index measuring the acromion and the lateral acromion angle have been standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…More recently, Banas et al 16 reported the association of the lateral inclination angle of the acromion with a higher prevalence of subacromial disease. These findings were also observed by Hanciau et al 17 Nevertheless, Nyffeler et al 4 introduced the concept of acromion index, suggesting that a greater lateral projection of the acromion would be a possible cause of this injury. Miyazaki et al 18 have confirmed this correlation for the Brazilian population.…”
Section: Discussionsupporting
confidence: 68%
“…More recently, Banas et al 16 reported the association of the lateral inclination angle of the acromion with a higher prevalence of subacromial disease. These findings were also observed by Hanciau et al 17 Nevertheless, Nyffeler et al 4 introduced the concept of acromion index, suggesting that a greater lateral projection of the acromion would be a possible cause of this injury. Miyazaki et al 18 have confirmed this correlation for the Brazilian population.…”
Section: Discussionsupporting
confidence: 68%